2023
DOI: 10.3390/healthcare11060893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pelvic-Tilt Imbalance on Disability, Muscle Performance, and Range of Motion in Office Workers with Non-Specific Low-Back Pain

Abstract: Imbalance in the pelvic tilt is considered to be a major variable in low back pain. The purpose of this study was to investigate the effects of pelvic-tilt imbalance on trunk- and hip-muscle performance, range of motion, low-back pain, and the degree of disability in office workers. This was a cross-sectional study conducted in a physical therapy clinic on forty-one office workers diagnosed with non-specific low-back pain. Among the office workers with non-specific low-back pain, 25 were assigned to the pelvic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The study also found a correlation of r=0.632 between the visual analogue scale and the neck disability score, showing that neck pain can induce moderate functional impairment in the neck [13]. Furthermore, weak muscles are thought to make it difficult to maintain balance and appropriate posture while performing daily duties, which raises the risk of pain and body asymmetry [6].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The study also found a correlation of r=0.632 between the visual analogue scale and the neck disability score, showing that neck pain can induce moderate functional impairment in the neck [13]. Furthermore, weak muscles are thought to make it difficult to maintain balance and appropriate posture while performing daily duties, which raises the risk of pain and body asymmetry [6].…”
Section: Discussionmentioning
confidence: 83%
“…It is therefore feasible to speculate that the posterior spinal muscles, through the thoracolumbar fascia, connect the lower trunk to the neck. Certain studies have shown a strong correlation between the cervical and pelvic spine's posture and the alignment of the complete spine [6,20,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, non-specific back pain implies no known pathoanatomical cause and is the most common reason for chronic low back pain - approximately 90% of cases [ [ 6 ]]. Unconscious movement patterns (such as lifting household items [ [ 7 ]]) typically cause this pain, which can result in hypertonic, painful muscles and reduced joint mobility [ [ 8 , 9 ]]. Conventional imaging methods such as X-ray or higher resolution imaging using Computed Tomography (CT) and Magnetic Resonance Imaging (MRI) [ [ 10 ]] primarily cannot detect these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lower back pain (LBP) is common and the leading cause of musculoskeletal disorder that frequently occurs because of muscle and ligament damage caused by excessive lower back movement and incorrect posture [ 1 ]. Back pain causes muscle weakness in the lower back, limits the range of motion of the joints [ 2 ], and leads to back instability due to asymmetrical spinal movements [ 3 ]. In LBP, the main aim of physical therapy and rehabilitation is to reduce pain and enhance motor function in the back area through various intervention methods, such as muscle strengthening, aerobic exercise, coordination exercise, corrective exercise, and trunk-centered exercise [ 4 ].…”
Section: Introductionmentioning
confidence: 99%